Intracranial bleeding risk after minor traumatic brain injury in patients on antithrombotic drugs. Issue 174 (February 2019) - Galliazzo, S.; Bianchi, M.D.; Virano, A.; Trucchi, A.; Donadini, M.P.; Dentali, F.; Bertù, L.; Grandi, A.M.; Ageno, W.
Abstract: Background: Intracranial haemorrhage (ICH) risk after minor traumatic brain injury (mTBI) in patients on antithrombotic treatment is unclear. We compared ICH rates in mTBI patients on single, double and no antithrombotic therapy. Antithrombotic drugs encompassed vitamin K antagonists (VKAs), direct oral anticoagulants (DOACs) and antiplatelets. Secondary aim was to identify potential predictors of ICH. Methods: We retrospectively analysed consecutive adults referred to our emergency department for mTBI. All clinical information was retrieved by patients' charts review. Patients were divided in 5 groups: 1) no antithrombotic users, 2) antiplatelet users, 3) vitamin K antagonist users, 4) direct oral anticoagulants users, and 5) double antithrombotic users. Results: A total of 1846 patients were enrolled, mean age 71 years (IQR 46–83); 1222 (66.2%) were in group 1, 407 (22.0%) in group 2, 120 (6.5%) in group 3, 51 (2.7%) in group 4 and 46 (2.5%) in group 5. At entry, 1387 (75.1%) patients underwent brain CT, 787 (64.4%) in group 1, 387 (95.1%) in group 2, 119 (99.2%) in group 3 and 51 (100%) in group 4 and 43 (93.5%) in group 5. ICH was documented in 36 patients (4.6%; CI 95%: 3.2–6.3) in group 1, 22 (5.9%; CI 95%: 3.6–8.5) in group 2, 5 (4.2%; CI 95%: 1.4–9.5) in group 3, 2 (3.9%; CI 95%: 0.5–13.5) in group 4 and 3 (7.0%; CI 95%: 1.5–19.1) in group 5 ( p -value for across groups comparison = 0.86). At multivariable analysis GCS < 15 (OR 7.95 CI 95%: 3.12–20.28), post-traumatic amnesia (OR 6.49; CI 95%:3.57–11.82), vomiting (OR 4.45 CI 95%:1.47–13.50), clinical signs of cranial fractures (OR 8.41 CI 95%: 2.12–33.33), scalp lesions (OR 2.31 CI 95%: 1.09–4.89), but none of antithrombotic drugs were independently associated with ICH. Conclusion: mTBI-related ICH rate was similar in patients with and without antithrombotic use. Potential predictors of ICH can be drawn from patients' clinical examination. Highlights: There is an increasing and unrestricted demand for emergency brain CT after minor traumatic brain injury. Some prediction models have been developed to select mTBI patients to be investigated by brain CT. Evidence to drive management strategies are lacking for antithrombotic drug users. Antithrombotic drugs do not appear as independent predictors of intracranial bleeding complications related to mTBI.